2014
DOI: 10.1111/nmo.12334
|View full text |Cite
|
Sign up to set email alerts
|

Natural compounds boldine and menthol are antagonists of human 5‐HT3 receptors: implications for treating gastrointestinal disorders

Abstract: The demonstrated 5-HT3 inhibitory effects may be relevant for boldine's and menthol's alleviating properties on FGID and may encourage clinical studies with the compounds or the plant extracts for CINV and IBS treatment. The found receptor-discriminative properties make boldine and (-)-menthol to potentially useful tools for analyzing structural differences between these receptor subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 45 publications
2
50
0
Order By: Relevance
“…In recent years, several natural plant ingredients have been identified as 5-HT 3A receptor blockers. These include the two terpenes (-)-menthol and α-thujone [7,23,24], However, effective concentrations of these blockers are typically in the high µM range. The potency of receptor block by ginsenosides from ginseng or gingerols from ginger is higher and lies in the range of 10 to 30 µM [11,25].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In recent years, several natural plant ingredients have been identified as 5-HT 3A receptor blockers. These include the two terpenes (-)-menthol and α-thujone [7,23,24], However, effective concentrations of these blockers are typically in the high µM range. The potency of receptor block by ginsenosides from ginseng or gingerols from ginger is higher and lies in the range of 10 to 30 µM [11,25].…”
Section: Discussionmentioning
confidence: 98%
“…The terpene (-)-menthol which is used against IBS (irritable bowel syndrome) also blocks 5-HT 3A receptors [7,23], but with a lower potency than citronellol. Presently, menthol is the only terpene with a described antiemetic action linked to 5-HT 3A inhibition [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, menthol has been hypothesized to exert antiemetic properties by inhibiting the cationic influx through 5-HT 3 receptor (Heimes et al, 2011) and it has been demonstrated to be an allosteric inhibitor of 5-HT 3 receptors using electrophysiological and biochemical methods (Ashoor et al, 2013b;Walstab et al, 2014). 5-HT 3 receptors are expressed by enteric sensory neurons in the mucosal layer and in the nerve cell body of interneurons and motor neurons in the enteric nervous system (Galligan, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…channels [5,6]. Carrying this research one step further, a recent study has also reported the L-menthol can also inhibit 5-HT 3 receptors in vitro, which may explain the decrease in the frequency and amplitude of gut contractions associated with PO [7].…”
mentioning
confidence: 99%